Surgical Aspects of Recurrent Macular Holes Treatment - A. N. Samoylov; T. R. Khaibrakhmanov; G. A. Khaibrakhmanova; P. A. Samoilova (Oftalʹmologiâ)
Despite the high level of development of modern macular surgery, recurrent macular holes remain a rather serious problem for vitreoretinal surgeons. Recurrent macular holes can be of two types: macular holes that have not closed after primary surgery, and macular holes that have reopened after a successful initial surgery. In foreign literature they are called persistent and recurrent macular holes. This article presents a review of modern scientific literature on epidemiology, causes of development and surgical treatment of recurrent macular holes. This review provides information on the rationality and effectiveness of modern surgical approaches to the treatment of this condition. The most effective methods for treating large macular holes, which are one of the main causes of failure to close a defect during the first surgery or the development of a recurrence of this condition sometime after the first surgery, are covered. Based on the literature data, we can say that the main methods of choice in surgery for recurrent macular holes today are the use of platelet-rich plasma and various modifications of the inverted internal limiting membrane flap technique, transplantation of the autologous internal limiting membrane, including the displaced internal limiting membrane flap technique patented in the Russian Federation.